2010
DOI: 10.3346/jkms.2010.25.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Drug Interaction between Warfarin and Nonsteroidal Anti-Inflammatory Drugs in Practical Setting

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are known to interact with the oral anticoagulant warfarin and can cause a serious bleeding complication. In this study, we evaluated the risk factors for international normalized ratio (INR) increase, which is a surrogate marker of bleeding, after addition of an NSAID in a total of 98 patients who used warfarin. Patient age, sex, body mass index, maintenance warfarin dose, baseline INR, coadministered medications, underlying diseases, and liver and kidney function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 24 publications
0
29
2
3
Order By: Relevance
“…The infection itself (inflammatory syndrome) may alter the warfarin metabolism or hepatic clotting factor synthesis 2,3) . Nonsteroidal anti-inflammatory drugs (NSAIDs) are known to interact with the oral anticoagulant warfarin and can cause serious bleeding complications 11,12) , although the results of this study failed to show significant relationship between the dose of NSAIDs and INR value.…”
Section: Discussioncontrasting
confidence: 49%
“…The infection itself (inflammatory syndrome) may alter the warfarin metabolism or hepatic clotting factor synthesis 2,3) . Nonsteroidal anti-inflammatory drugs (NSAIDs) are known to interact with the oral anticoagulant warfarin and can cause serious bleeding complications 11,12) , although the results of this study failed to show significant relationship between the dose of NSAIDs and INR value.…”
Section: Discussioncontrasting
confidence: 49%
“…Similar to this, Choi et al . . showed that almost 40% of patients on warfarin had an INR increase after initiation of a NSAID with the highest risk from meloxicam and lower risk from naproxen, celecoxib and ibuprofen.…”
mentioning
confidence: 99%
“…In one study, it was shown that the risk of using NSAIDs is higher in patients who are on >40 mg/week of warfarin . Although generally the combined use of NSAIDs with anticoagulant agents is discouraged, this study was conducted on patients who were using NSAIDs daily.…”
Section: Common Abortive Headache Medicationsmentioning
confidence: 99%
“…In one study, it was shown that the risk of using NSAIDs is higher in patients who are on >40 mg/week of warfarin. 6 Although generally the combined use of NSAIDs with anticoagulant agents is discouraged, this study was conducted on patients who were using NSAIDs daily. Since in headache medicine NSAIDs are typically used on an "as needed" basis (except in some uncommon headache disorder such as hemicrania continua), there are no supporting data for recommendations on how to readjust the anticoagulant dose (specifically warfarin) in the setting of daily NSAID use.…”
Section: Anticoagulantsmentioning
confidence: 99%